Gold Nanoparticle-Functionalized Diatom Biosilica as Label-Free Biosensor for Biomolecule Detection - Chen, Tongtong; Wu, Feifei; Li, Yang; Rozan, Hussein E.; Chen, Xiguang; Feng, Chao (Frontiers in Bioengineering and Biotechnology, 2022)
Diatom biosilica (DBs) is cell wall of natural diatom called frustule, which is made of porous hydrogenated amorphous silica possessing periodic micro- to the nanoscale features. In this study, a simple, sensitive and label-free Photoluminescence (PL) immune-detection platform based functionalized diatom frustules was developed. Gold nanoparticles (AuNPs) deposited on poly-dopamine coated diatom frustules via in-situ deposition which considerably decreased the intrinsic blue PL intensity of diatom biosilica. Then, goat anti rabbit immunoglobulin G (IgG) was added to functionalize diatom biosilica-poly-dopamine-AuNPs (DBs-PDA-AuNPs). PL studies revealed the specific binding with antigen rabbit IgG increased the peak intensity of PL in comparison with the non-complimentary antigen (human IgG). The enhancement in PL intensity of DBs-PDA has linear correlation with antigen (rabbit IgG) concentration, whose limit of detection (LOD) reaches 8*10-6 mg/mL. Furthermore, PL detection based on DBs-PDA-AuNPs showed a high detection sensitivity with the LOD as low as 8*10-9 mg/mL and spread over almost 8 orders of magnitude, made it suitable for the sensitive quantitative analysis of immune complex compared with traditional fluorescence immunoassay. Hence, the study proves that the AuNPs functionalized diatom frustules can serve as an effective biosensor platform for label-free PL-based immunoassay.